Pelatihan Patient Centered Care pada Mahasiswa Bidan Meningkatkan Kesejahteraan Pasien Post SC - Sulistianto, Henri; Maretta, Megayana Yessy; Andhikatias, Yunia Renny (Yumary: Jurnal Pengabdian kepada Masyarakat, 2023)
Purpose: This Community Service activity aims to increase the knowledge and attitudes of midwife students about Patient Centered Care (PCC), which is one of the efforts to improve the wellbeing of Post SC patients. Methodology/approach: This activity was carried out on Wednesday, April 12 2023 with the target of Midwifery students Semester IV and VI, Mega Buana University, Palopo, South Sulawesi. Community service activities are carried out through 3 stages, namely 1) Pretest; 2) Training carried out using lecture and question and answer methods as well as demonstrations via zoom meeting media; 3) Posttest. Data was collected using questionnaire data collection techniques and document study. Results/findings: The majority of students have a good level of knowledge (62%) about PCC with a p value = 0.014 and the majority have a good attitude (71%) about PCC with a p value = 0.021 after training. Conclusion: PCC training is effective in increasing the knowledge and attitudes of midwife students and can be an alternative in improving the wellbeing of post-SC patients as indicated by reduced levels of anxiety and increased satisfaction of post-SC patients. Keywords: PCC, students, midwives, knowledge, attitudes